Sea clutter scattering, the K distribution and radar performance - Ward, Keith D.; Tough, Robert J. A.; Watts, Simon 1949- (London, United Kingdom The Institution of Engineering and Technology, 2013)
The book covers five parts. Part one belongs to sea clutter properties. Part two discusses the mathematics of the K-distribution. Part three covers the radar detection and Part four deals with physical modelling of radar.
Electronic reproduction.
Keywords: Incoherent scatter radar; Radar -- Interference -- Mathematical models; Boats and boating -- Radar equipment; Electromagnetic waves -- Scattering; Radar; Electronic books